FIGURE 11. Floriaster maya. A in New species, occurrence records and observations of predation by deep-sea Asteroidea (Echinodermata) from the North Atlantic by NOAA ship Okeanos Explorer - Mah, Christopher L. (Zenodo, 2020)
FIGURE 11. Floriaster maya. A. In situ feeding observation Berg Bits. B. In situ feeding observation Mona South Ridge, 1156 m. C. Abactinal surface. Scale bar=1.0 cm. D. Actinal surface. Scale bar=1.0 cm. E. Abactinal-lateral surface. Scale bar=0.5 cm. : Published as part of Mah, Christopher L., 2020, New species, occurrence records and observations of predation by deep-sea Asteroidea (Echinodermata) from the North Atlantic by NOAA ship Okeanos Explorer, pp. 201-260 in Zootaxa 4766 (2) on page 227, DOI: 10.11646/zootaxa.4766.2.1, http://zenodo.org/record/3764018